RalA and RalB Proteins Are Ubiquitinated GTPases, and Ubiquitinated RalA Increases Lipid Raft Exposure at the Plasma Membrane - Neyraud, Vincent (American Society for Biochemistry and Molecular Biology, 2012)
Ras GTPases signal by orchestrating a balance among several effector pathways, of which those driven by the GTPases RalA and RalB are essential to Ras oncogenic functions. RalA and RalB share the same effectors but support different aspects of oncogenesis. One example is the importance of active RalA in anchorage-independent growth and membrane raft trafficking. This study has shown a new post-translational modification of Ral GTPases: nondegradative ubiquitination. RalA (but not RalB) ubiquitination increases in anchorage-independent conditions in a caveolin-dependent manner and when lipid rafts are endocytosed. Forcing RalA mono-ubiquitination (by expressing a protein fusion consisting of ubiquitin fused N-terminally to RalA) leads to RalA enrichment at the plasma membrane and increases raft exposure. This study suggests the existence of an ubiquitination/de-ubiquitination cycle superimposed on the GDP/GTP cycle of RalA, involved in the regulation of RalA activity as well as in membrane raft trafficking.